USE OF SENGGANI LEAVES AS AN ALTERNATIVE MATERIAL FOR PRINTER REFILL INK THAT IS LOW VOC (VOLATILE ORGANIC COMPOUND) ENVIRONMENTALLY FRIENDLY - Trilia Ananta Pramita Sari; Rewan Jayadi; Rika Agustin; Putri Ramanda; Nurhasana; Eka Angasa (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This study aims to determine the content of senggani leaves and utilize senggani leaves as a raw material for printer refill ink. This can increase the utilization of senggani leaves into products that are low in VOC levels. The method used in this study the first test is done, the ink absorption rate test on HVS paper is done by using a medium such as paper by comparing the length of the absorption path ∆x with a time interval t during the absorption process. The next test is the ink performance test using the volume of aqueous solvent and comparing the quality of the ink obtained. The ink consists of 3 components, namely pigment, solvent, and thickening agent the pigment used in this study is carbon obtained from the carbonization of senggani leaves, 98% alcohol is used as a carbon solvent as a thickener and adhesive in the form of gum arabic. The variation of carbon used is 1 gram, 2 grams, and 3 grams, while the volume of aquadest, the volume of alcohol, and gum arabic mass is made fixed that is sequentially 15 mL, 3 mL, and 3.5 grams. The test results of senggani leaf ink with the best composition resulted in solvent and mass variation values by the standard. Meanwhile, from the results of the print test, the resulting printer ink has provided good print and color results as well as commercial ink and does not easily fade if exposed to water. Keywords: senggani leaf, ink, pigment.